3D in vitro Models of Pathological Skeletal Muscle: Which Cells and Scaffolds to Elect? - Carraro, Eugenia; Rossi, Lucia; Maghin, Edoardo; Canton, Marcella; Piccoli, Martina (Frontiers in Bioengineering and Biotechnology, 2022)
Skeletal muscle is a fundamental tissue of the human body with great plasticity and adaptation to diseases and injuries. Recreating this tissue in vitro helps not only to deepen its functionality, but also to simulate pathophysiological processes. In this review we discuss the generation of human skeletal muscle three-dimensional (3D) models obtained through tissue engineering approaches. First, we present an overview of the most severe myopathies and the two key players involved: the variety of cells composing skeletal muscle tissue and the different components of its extracellular matrix. Then, we discuss the peculiar characteristics among diverse in vitro models with a specific focus on cell sources, scaffold composition and formulations, and fabrication techniques. To conclude, we highlight the efficacy of 3D models in mimicking patient-specific myopathies, deepening muscle disease mechanisms or investigating possible therapeutic effects.